An overview of dissolved Fe and Mn distributions during the 2010–2011 U.S. GEOTRACES north Atlantic cruises: GEOTRACES GA03. (June 2015) - Hatta, Mariko; Measures, Chris I.; Wu, Jingfeng; Roshan, Saeed; Fitzsimmons, Jessica N.; Sedwick, Peter; Morton, Pete
Abstract: High-resolution dissolved Fe (dFe) and dissolved Mn (dMn) distributions were obtained using a trace metal clean rosette during the GEOTRACES GA03 zonal transect cruises (USGT10 and USGT11) across the North Atlantic Ocean. This manuscript provides a general overview of the dFe, as well as dMn and dissolved Al (dAl) distributions that reveal several Fe inputs at varying depths across the study region. Elevated dFe concentrations correlate with elevated dAl concentrations in the surface waters of the subtropical gyre, indicating a significant atmospheric source of Fe, in contrast there is no apparent significant dust source for Mn. In the subsurface waters, dFe maxima are a result of the remineralization process, as revealed by their correspondence with dissolved oxygen minima. Within the oxygen minimum, the ratio of dFe to apparent oxygen utilization (AOU) is lower than would be expected from the measured Fe content of surface water phytoplankton, suggesting that a significant amount of dFe that is remineralized at depth ( 63–90%) is subsequently scavenged from the water column. The rate of remineralization, which is based on the slope of dFe:AOU plot, is similar across a wide area of the North Atlantic. In addition to the remineralization process, sedimentary inputs are apparent from elevated dMn signals in the eastern basin, particularly near the African coast. In the western basin, sedimentary input is also occurring along the advective flow path of the Upper Labrador Sea Water (ULSW), as ULSW transits along the North American continental shelf region. The largest dFe anomaly ( 68 nM), which also corresponds to a dMn anomaly (up to 33 nM) is seen in the neutrally buoyant hydrothermal plume sampled over the Mid-Atlantic Ridge, and that signal is visible for 500 km to the west of the ridge.